1989
DOI: 10.1016/0014-5793(89)80799-9
|View full text |Cite
|
Sign up to set email alerts
|

A cDNA clone encoding the precursor for a 10.2 kDa photosystem I polypeptide of barley

Abstract: Two cDNA clones for the barley photosystem I polypeptide which migrates with an apparent molecular mass of 9.5 kDa on SDS-polyacrylamide gels have been isolated using antibodies and an oligonucleotide probe. The determined N-terminal amino acid sequence for the mature polypeptide confirms the identification of the clones. The 644 base-pair sequence of one of the clones contains one large open reading frame coding for a 14,882 Da precursor polypeptide. The molecular mass of the mature polypeptide is 10 193 Da. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

1990
1990
1999
1999

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(11 citation statements)
references
References 36 publications
0
11
0
Order By: Relevance
“…The primary structure of most of the PSI subunits has been determined and most have been sequenced for barley [12,19,20,22,23,27]. Cross-linking, antibody inhibition and reconstitution studies have shown that PSI-D and PSI-E The nucleotide sequence data reported will appear in the EMBL, Genbank and DDBJ Nucleotide Sequence Databases under the accession number X66428.…”
Section: Introductionmentioning
confidence: 99%
“…The primary structure of most of the PSI subunits has been determined and most have been sequenced for barley [12,19,20,22,23,27]. Cross-linking, antibody inhibition and reconstitution studies have shown that PSI-D and PSI-E The nucleotide sequence data reported will appear in the EMBL, Genbank and DDBJ Nucleotide Sequence Databases under the accession number X66428.…”
Section: Introductionmentioning
confidence: 99%
“…The DNA constructs used in this study were pBluescript plasmids containing cDNA inserts encoding the precursors of barley PSI-H [15], barley PSI-L [17], and barley PSI-G (this paper). Preparation of the radiolabelled precursors and the import assays were performed essentially according to Dahlin and Cline [4].…”
Section: Methodsmentioning
confidence: 99%
“…Twelve different protein subThe nucleotide sequence data reported will appear in the EMBL, GenBank and DDBJ nucleotide sequence databases under the accession number X60t58. units have been identified in PSI core complexes and their primary structure have been determined from different species (for recent reviews see [1,31. In higher plants and algae five of the subunits are chloroplast-encoded (PSI-A, -B, -C, -I, -J) and seven are nuclear-encoded (PSI-D, -E, -F, -G,-H, -K, -L) using a designation of the subunits according to their corresponding genes psaA to PsaL, where in barley psa indicates a chloroplast gene and Psa indicates a nuclear gene [9,15]. Previously no sequence similarity between the nuclear-encoded subunits have been reported except for the N-terminal part of barley PSI-D and PSI-E [19].…”
Section: Introductionmentioning
confidence: 99%
“…Recently it became clear that gene GOS5 corresponds with the barley gene psaH encoding a 9.5 kDa photosystem I polypeptide [42]. The single-copy rice gene contains two intron sequences (125 and 77 nucleotides; Fig.…”
Section: Introductionmentioning
confidence: 99%